Retrospective Analysis of Surgical Outcomes Following Scarless Orchiopexy via Either Scrotal Incision or Single-Site Transumbilical Laparoscopy - Zhang, Chu; Tian, Qingqing; Zhao, Xiang; Yu, Kechi; Cao, Peng; Niu, Yonghua; Zhou, Xuefeng; Li, Ning (Urology Journal, 2025)
Purpose: The surgical approach to pediatric cryptorchidism has traditionally been the inguinal pathway. However, that has changed with the increased use of scrotal incision and single-site transumbilical laparoscopy, both of which result in a scarless surgical incision. We aimed to review our experience with the combined utilization of these two methods for the treatment of pediatric cryptorchidism and evaluate the surgical outcomes. Materials and Methods: This retrospective case series included 267 children who underwent scarless orchiopexy between January 2019 and December 2022. Data were gathered from case and operative records. Testicular retraction, testicular atrophy, other complications, cosmetic outcomes, and parental satisfaction were evaluated. Results: A total of 267 children (aged 1–7.4 years, median 1.8 years) with palpable and nonpalpable undescended testes underwent scarless orchiopexy at our center. Among them, 58 (21.7%) were treated with a scrotal incision and 209 (78.3%) underwent single-site transumbilical laparoscopic surgery. The follow-up period ranged from 6 to 53 months, with an average of 26.2 months. During the follow-up period, testicular retraction (4 cases, 1.5%) and atrophy (5 cases, 1.9%) occurred in the laparoscopic group. One child in the laparoscopic group developed a hydrocele but recovered after 3 months. In most cases (98.9%), the scars were invisible, indicating an excellent cosmetic effect. Conclusion: The combination of scrotal incision and transumbilical laparoscopic orchiopexy can resolve cryptorchidism in children at different locations and achieve successful outcomes with a low rate of postoperative complications and good cosmetic results.